Seven years’ experience with alendronate in postmenopausal Japanese women with osteoporosis - Jun Iwamoto; Yoshihiro Sato; Mitsuyoshi Uzawa; et al (Dove Medical Press, 2010)
Jun Iwamoto1, Yoshihiro Sato2, Mitsuyoshi Uzawa3, Tsuyoshi Takeda1, Hideo Matsumoto11Institute for Integrated Sports Medicine, Keio University School of Medicine, Tokyo, Japan; 2Department of Neurology, Mitate Hospital, Fukuoka, Japan; 3Department of Orthopaedic Surgery, Keiyu Orthopaedic Hospital, Gunma, JapanAbstract: A retrospective study was performed to evaluate the outcome of alendronate (ALN) treatment for seven years in postmenopausal Japanese women with osteoporosis. Forty-seven postmenopausal women with osteoporosis (mean age at baseline 65.7 years) treated with ALN for over seven years in our outpatient clinic were analyzed. Lumbar spine bone mineral density (BMD) was measured using dual energy X-ray absorptiometry, and urinary levels of cross-linked N-terminal telopeptides of type I collagen (NTX) and serum alkaline phosphatase (ALP) were monitored during the seven-year treatment period. Urinary NTX and serum ALP levels decreased (-48.2% at three months and -15.7% at seven years, respectively) and lumbar spine BMD increased (+12.8% at seven years) compared with baseline values. No serious adverse events were observed, including osteonecrosis of jaw, atypical femoral diaphysis fractures, or atrial fibrillation. To our knowledge, this is the first report of the outcome of ALN treatment for seven years in Japanese patients with osteoporosis. ALN successfully suppressed bone turnover and increased lumbar spine BMD from the baseline value over the course of the seven-year treatment period without causing any severe adverse events.Keywords: alendronate, osteoporosis, long-term treatment, bone mineral density, bone turnover